Harmonizing Measures of Cognitive Performance Across International Surveys of Aging Using Item Response Theory. (December 2015) - Chan, Kitty S.; Gross, Alden L.; Pezzin, Liliana E.; Brandt, Jason; Kasper, Judith D.
Objective: To harmonize measures of cognitive performance using item response theory (IRT) across two international aging studies.Method: Data for persons ≥65 years from the Health and Retirement Study (HRS, N = 9, 471) and the English Longitudinal Study of Aging (ELSA, N = 5, 444). Cognitive performance measures varied (HRS fielded 25, ELSA 13); 9 were in common. Measurement precision was examined for IRT scores based on (a) common items, (b) common items adjusted for differential item functioning (DIF), and (c) DIF-adjusted all items.Results: Three common items (day of date, immediate word recall, and delayed word recall) demonstrated DIF by survey. Adding survey-specific items improved precision but mainly for HRS respondents at lower cognitive levels.Discussion: IRT offers a feasible strategy for harmonizing cognitive performance measures across other surveys and for other multi-item constructs of interest in studies of aging. Practical implications depend on sample distribution and the difficulty mix of in-common and survey-specific items.